Experiences of cognitive coaching - Gyllensten, Kristina; Palmer, Stephen; Nilsson, Eva-Karin; Regnér, Agneta Meland; Frodi, Ann (Coaching Psykologi - The Danish Journal of Coaching Psychology, 2012)
Objectives: Cognitive coaching and cognitive behavioural coaching are approaches practiced by many coaching psychologists (Palmer & Whybrow, 2007). However, there is a lack of qualitative studies evaluating these approaches. The main objective of/with the present study was to investigate a number of participants’ experiences of cognitive coaching.